Towards Green Growth and Socio-Ecological Justice: An Evaluation of Governance Policies, Multi-Sector Impacts, and Sustainable Tourism Development Strategies in Bali - I Gede Made Widyanata; Nyoman Diah Utari Dewi; Anurat Anantanathorn (Contemporary Public Administration Review, 2026)
Tourism in Bali Province faces a critical turning point where macroeconomic growth frequently clashes with environmental carrying capacity and social justice. This study evaluates tourism governance policies in Bali by examining multi-sector impacts, public narratives, and strategic development frameworks. Employing an explanatory sequential mixed-methods design, the study first analyzed 20 purposively selected online news articles (2025–2026) using Robert Entman’s framing analysis to map public discourses regarding governance failures and socio-ecological crises. These secondary findings were then empirically validated and triangulated through a survey of 30 Balinese youth respondents across urban/southern and buffer zones, supplemented by in-depth qualitative interviews with community youth leaders. The analysis reveals a pronounced policy decoupling between formal regulations (such as Regional Regulation No. 5/2020 and the Foreign Tourist Levy) and field enforcement, resulting in an acute groundwater crisis, rampant conversion of subak agricultural land, spatial gentrification, and socio-cultural friction. The empirical survey strongly corroborated media narratives, particularly regarding land unaffordability (96.6%) and non-transparent ecological tax governance (93.3%–96.6%). To address these structural failures, this article delineates an analytical pathway toward a Green Growth framework, proposing a strict moratorium on southern accommodation permits, mandatory earmarking of tourist levies for subak preservation, and youth-led digital governance anchored in Tri Hita Karana.